Pembentukan Posisi Perempuan dalam Novel ‘Pride and Prejudice’ Karya Jane Austen - Sabrina Wardatul Jannah Husain (BUANA GENDER : Jurnal Studi Gender dan Anak, 2020)
This study aims to determine the formation of women's position in the novel Pride and Prejudice by Jane Austen. This study also aims to determine the reasons behind the placement of the women's positions which are depicted in the novel. This novel is a classic romance novel one of the realistic writings written by Jane Austen that describes the position of women based on their social status. The intersection theory is used to see the process of forming the positions and reasons behind it. In this case, the determination of these positions is formed through social class, identity, abilities (skills) and physical form that women have. The intersection case studies that shape women's identities are influenced by history, culture, and ideology, as well as the representation of this discourse, giving women the treatment of gender discrimination, oppression, and oppression.